Redistribution in a Bifurcated Welfare State: Quintile Shares and the U.S. Case. (4th August 2014) - Devine, Joel A.; Canak, William
Abstract : The present analysis is part of an ongoing study of the determinants, structure, and consequences of the U.S. welfare state. In this paper, we explore the bifurcated structure of U.S. social welfare spending, the differential growth of "social consumption" and "social expense" outlays, and the redistributional impact of these expenditures on quintile shares of personal income. Results of a time-series regression analysis (1949–1977) indicate that, in relative terms, social welfare expenditures have not been progressively redistributive.